PONDOK PESANTREN EKOLOGI AT THORIQ: Dari Sustainability Alam Menuju Kemandirian Ekonomi - Maula, Inayatul (Jurnal Pendidikan Islam, 2022)
This research will examine two important issues, first, issues related to ecology with all the scope of the problem. Second, issues related to economic independence. These two important issues are underwritten by Pondok Pesantren as a basis and value in solving ecological problems and economic independence. Theoretical studies of Islamic boarding schools' values originating from the treasures of "yellow yellow" are translated into practical matters. In summary, this research will also confirm that the treasures of the “Yellow Book” which contains a lot of ethical content can be implemented in more real actions, namely taking sides on ecological issues and issues of economic independence. This research uses a qualitative approach to the type of case study research. The thing that underlies the use of a qualitative approach in this research is because the researcher will explore the problem and develop a more detailed understanding of the phenomenon. Sources of data in this study were obtained from Caregivers/Leaders of the At Thoriq Ecology Islamic Boarding School, Management, Santri and the community around the Islamic Boarding School who were actively involved in the activity process. Data collection techniques were carried out by in-depth interviews, participatory observation and documentation. Qualitative data analysis techniques are carried out interactively, continuously until they reach completeness so as to obtain saturated data. Activities in data analysis are data reduction, data display and conculsion drawing/verification. The results of this study obtained information that products produced from agroecological activities developed by the At Thoriq Ecology Islamic Boarding School such as herbal teas, beauty products, organic rice, etc. are able to support Islamic boarding school activities so that Islamic boarding schools can be independent.